LncRNA RP11-138J23.1 Contributes to Gastric Cancer Progression by Interacting With RNA-Binding Protein HuR - Xu, Yongcan; Yu, Xiang; Xu, Jing; Lu, Jun; Jiang, Hao; Lou, Neng; Lu, Wei; Xu, Jiewei; Ye, Guochao; Dong, Shunli; Nie, Fengqi (Frontiers in Oncology, 2022)
In spite of improvements in diagnostics and treatment of gastric cancer (GC), it remains the most common malignancy of human digestive system. It is now widely appreciated that long non-coding RNAs (lncRNAs) exert extensive regulatory effects on a spectrum of fundamental biological processes through diverse mechanisms. In this study, we explored the expression level and functional role of lncRNA RP11-138J23.1 in GC. Through bioinformatics analyses and In Situ Hybridization (ISH), we identified that RP11-138J23.1 was upregulated in GC tissue. Further study showed that RP11-138J23.1 knockdown significantly inhibited cell proliferation and metastatic ability. While, RP11-138J23.1 overexpression could increase tumor cell growth and metastasis in vitro. Additionally, loss-of-function assays conducted by shRNA were used to confirm the role of RP11-138J23.1 in vivo. Mechanistically, RP11-138J23.1 exerted its oncogenic functions by binding to HuR protein and increasing stability of VAV3 mRNA. Overall, our study highlights the essential role of RP11-138J23.1 in GC, suggesting that RP11-138J23.1 might be a potent therapeutic target for patients with GC.